2017
DOI: 10.1016/j.stem.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

An endosiRNA-Based Repression Mechanism Counteracts Transposon Activation during Global DNA Demethylation in Embryonic Stem Cells

Abstract: SummaryErasure of DNA methylation and repressive chromatin marks in the mammalian germline leads to risk of transcriptional activation of transposable elements (TEs). Here, we used mouse embryonic stem cells (ESCs) to identify an endosiRNA-based mechanism involved in suppression of TE transcription. In ESCs with DNA demethylation induced by acute deletion of Dnmt1, we saw an increase in sense transcription at TEs, resulting in an abundance of sense/antisense transcripts leading to high levels of ARGONAUTE2 (AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 47 publications
7
58
0
Order By: Relevance
“…In contrast to imprinted domains, this was only modestly correlated with changes in expression of nearby genes suggesting a functionally distinct role for ZFP57 at these regions. With few notable exceptions, TEs maintained H3K9me3 supporting the idea that they may be transcriptionally silenced by multiple redundant mechanisms involving other KZFPs in ES cells [4,6,25,26]. This pattern of retained H3K9me3 was also observed in ES cells derived from embryos with maternal-zygotic ZFP57 deletion.…”
Section: Main Textsupporting
confidence: 58%
“…In contrast to imprinted domains, this was only modestly correlated with changes in expression of nearby genes suggesting a functionally distinct role for ZFP57 at these regions. With few notable exceptions, TEs maintained H3K9me3 supporting the idea that they may be transcriptionally silenced by multiple redundant mechanisms involving other KZFPs in ES cells [4,6,25,26]. This pattern of retained H3K9me3 was also observed in ES cells derived from embryos with maternal-zygotic ZFP57 deletion.…”
Section: Main Textsupporting
confidence: 58%
“…Among mechanistic possibilities linking TE's activation to ME/CFS symptoms, hypomethylation of genomic regions could trigger transcriptional activation of otherwise silent TEs, leading to innate immune response in a noninfectious scenario 146 as well as compromising production of cellular miRNAs. 139 Interestingly, LPS stimulation alters the retrotransposon transcriptome in PBMCs. 144 Future literature screenings of TEs associated with specific ME/CFS epigenetic marks following the design presented here may help identify particular repetitive elements to be questioned by using approaches focused on cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increasing evidence shows that pervasive exaptation of TEs provide, in addition to promoter binding sites, a profusion of additional cis-acting regulatory elements, including enhancers, insulators, and repressive elements that contribute to regulation of transcription by both RNA polymerase II and III. 103,104,130,132,136e138 Moreover, Berrens et al 139 have shown that increased transcription of sense TEs occurs in response to genome hypomethylation, leading to sequestration of AGO2 with small RNA complexes produced by hybridization of sense and pervasive antisense TE transcription products, reciprocally affecting miRNA biogenesis.…”
Section: Genomic Location Associations Between Me/cfs De Ncrnas and Tesmentioning
confidence: 99%
“…To investigate how the different biases affect the final quantitation of methylation in genomic features we analysed two sets of data: 1) Set 1 included the previously used public mESCs WGBS datasets prepared with six different protocols by different teams [29,31,36,39,40,48,49] and 2) Set 2 included a combination of 'PBAT' and BS-seq 'Heat' datasets from four different biological samples (mESC, blastocyst, oocyte and sperm) prepared by a single team [29].…”
Section: Effect On Quantitation Of Methylationmentioning
confidence: 99%